The plant growth promoting substance, lumichrome, mimics starch and ethylene-associated symbiotic responses in lotus and tomato roots - Gouws, Liezel; Botes, Eileen; Wiese, Anna J.; Trenkamp, Sandra; Torres-Jerez, Ivone; Tang, Yuhong; Hills, Paul N.; Usadel, Bjoern; Lloyd, James R.; Fernie, Alisdair; Kossmann, Jens; Van Der Merwe, Margaretha J. (Frontiers in Plant Science, 2012)
Symbiosis involves responses that maintain the plant host and symbiotic partner’s genetic program; yet these cues are far from elucidated. Here we describe the effects of lumichrome, a flavin identified from Rhizobium spp., applied to lotus (Lotus japonicus) and tomato (Solanum lycopersicum). Combined transcriptional and metabolite analyses suggest that both species shared common pathways that were altered in response to this application under replete, sterile conditions. These included genes involved in symbiosis, as well as transcriptional and metabolic responses related to enhanced starch accumulation and altered ethylene metabolism. Lumichrome priming also resulted in altered colonization with either Mesorhizobium loti (for lotus) or Glomus intraradices/Glomus mossea (for tomato). It enhanced nodule number but not nodule formation in lotus; while leading to enhanced hyphae initiation and delayed arbuscule maturation in tomato.